2013
DOI: 10.1002/jms.3298
|View full text |Cite
|
Sign up to set email alerts
|

Specificity enhancement by electrospray ionization multistage mass spectrometry – a valuable tool for differentiation and identification of ‘V’‐type chemical warfare agents

Abstract: The use of chemical warfare agents has become an issue of emerging concern. One of the challenges in analytical monitoring of the extremely toxic 'V'-type chemical weapons [O-alkyl S-(2-dialkylamino)ethyl alkylphosphonothiolates] is to distinguish and identify compounds of similar structure. MS analysis of these compounds reveals mostly fragment/product ions representing the amine-containing residue. Hence, isomers or derivatives with the same amine residue exhibit similar mass spectral patterns in both classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, difficulties arise in cases where the ESI‐MS/MS spectrum is uninformative or exhibits poor quality, leading to insufficient evidence to match the ESI‐MS/MS spectra to the proposed structure. Several compounds containing an amine side chain, particularly tertiary amines, present information‐poor mass spectra with product ions mostly/only representing the amine‐containing residue . This lack of information is attributed to the strong tendency of the amine side chain to stabilize the positive charge and leads to unavoidable ambiguity in the identification process.…”
Section: Introductionmentioning
confidence: 99%
“…However, difficulties arise in cases where the ESI‐MS/MS spectrum is uninformative or exhibits poor quality, leading to insufficient evidence to match the ESI‐MS/MS spectra to the proposed structure. Several compounds containing an amine side chain, particularly tertiary amines, present information‐poor mass spectra with product ions mostly/only representing the amine‐containing residue . This lack of information is attributed to the strong tendency of the amine side chain to stabilize the positive charge and leads to unavoidable ambiguity in the identification process.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the SIL analogs resulted in better calculated LODs for TMP and DIMP. In the case of DMMP, d 9 TMP yielded the more reproducible results than when using 13 Cd 3 DIMP as the ISTD. These differences are likely because both DMMP and d 9 TMP are protonated ions, whereas 13 Fig.…”
Section: Resultsmentioning
confidence: 93%
“…8 Analysis of CWAs by mass spectrometry (MS) has grown substantially in the last 10 years. [9][10][11][12][13] Many of the fielded MS methods require the use of gas chromatography (GC) and/or liquid chromatography (LC), which pose difficulties for rapid analysis due to sample preparation needs 14 and lengthy run times. Several rapid, on-site methods have been proposed, such as atmospheric pressure chemical ionization (APCI) MS, 15,16 selected ion flow tube (SIFT) MS, 17,18 and proton transfer reaction (PTR) MS. 19 However, these methods can only measure a limited range of volatile small molecules and have strong carry-over between runs, which decreases the rate of sample analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been implemented for the structural elucidation of V‐nerve agent derivatives and their isomers. Weissberg et al 8 and Housman et al 9 demonstrated the use of ESI‐MS 2 and ESI‐MS 3 experiments in cases where the information derived from routine ESI‐MS 2 experiments was insufficient for structural elucidation. More recently, Snyder et al 2 demonstrated the applicability of a single‐linear quadrupole ion trap to acquire two‐dimensional mass spectrometry data (2D MS/MS) for the identification of V‐nerve agents.…”
Section: Introductionmentioning
confidence: 99%